Students’ Perception: Students’ Digital Literacy Skill in Senior High School - kasriyati, destina; Andriani, Refika; Kurniawan, Kurniawan; Syalshabillah, Aura (J-SHMIC : Journal of English for Academic, 2024)
Technology is currently developing rapidly, all elements including the world of education are also experiencing this development. There is no doubt that digital-based technology has been enjoyed by educators and students in school learning as an information medium for exploring knowledge. This study is aimed to identify the students’ perception towards digital literacy. This research used quantitative  with survey approach. The instrumen of this research is questionnaire. Questionnaire was distributed to the students by google form.  In other words, the results of this research are students’ perception of digital literacy can be categorized moderate level with score 2,94. It can be concluded that the internet is a very important  for students, especially for searching information and doing school assignments. The implication of this research that considering the importance of the internet for students, there needs to be education about online security, privacy and ethics of internet use so that students can be wiser in searching for information.